Engineering-oriented simulation platform for laminar cooling process of hot rolled strips. (2015) - Pian, Jinxiang; Wang, Zhen; Zhu, Yunlong; Chai, Tianyou; Li, Jiejia
Because the new approach cannot be applied directly in the hot-rolled strip laminar cooling process, a simulation is necessary to verify the new approach effectively which can improve the strip quality and production yields. In order to make sure simulation platform is similar to the practical industrial process as much as possible, we proposed an engineering-oriented distributed simulation platform for laminar cooling process, integrating part of physical equipment (such as PLC). Additionally, there is physical signals exchange among the controller and virtual sensors in the platform. The simulation platform consists of four parts, including virtual object, virtual instruments and actuators, loop controller and process monitoring computer, and setting controller. The virtual object reflects the actual input and output characteristics of laminar cooling process. Virtual instruments and actuators can simulate the field instruments and actuators. Loop controller and process monitoring show the device operating conditions, the control performance, and give alarm signals in time. Setting controller performs setting control procedures. The experimental results indicate that simulation platform has powerful ability to evaluate the new approach in light of the engineering, which can reduce the live-fire testing cost and meet the requirements of repeated trials.